New insights into donor directionality of mating-type switching in Schizosaccharomyces pombe. - Takahisa Maki; Naoto Ogura; James E Haber; Hiroshi Iwasaki; Geneviève Thon (PLoS Genetics)
Mating-type switching in Schizosaccharomyces pombe entails programmed gene conversion events regulated by DNA replication, heterochromatin, and the HP1-like chromodomain protein Swi6. The whole mechanism remains to be fully understood. Using a gene deletion library, we screened ~ 3400 mutants for defects in the donor selection step where a heterochromatic locus, mat2-P or mat3-M, is chosen to convert the expressed mat1 locus. By measuring the biases in mat1 content that result from faulty directionality, we identified in total 20 factors required for donor selection. Unexpectedly, these included the histone H3 lysine 4 (H3K4) methyltransferase complex subunits Set1, Swd1, Swd2, Swd3, Spf1 and Ash2, the BRE1-like ubiquitin ligase Brl2 and the Elongator complex subunit Elp6. The mutant defects were investigated in strains with reversed donor loci (mat2-M mat3-P) or when the SRE2 and SRE3 recombination enhancers, adjacent to the donors, were deleted or transposed. Mutants in Set1C, Brl2 or Elp6 altered balanced donor usage away from mat2 and the SRE2 enhancer, towards mat3 and the SRE3 enhancer. The defects in these mutants were qualitatively similar to heterochromatin mutants lacking Swi6, the NAD+-dependent histone deacetylase Sir2, or the Clr4, Raf1 or Rik1 subunits of the histone H3 lysine 9 (H3K9) methyltransferase complex, albeit not as extreme. Other mutants showed clonal biases in switching. This was the case for mutants in the NAD+-independent deacetylase complex subunits Clr1, Clr2 and Clr3, the casein kinase CK2 subunit Ckb1, the ubiquitin ligase component Pof3, and the CENP-B homologue Cbp1, as well as for double mutants lacking Swi6 and Brl2, Pof3, or Cbp1. Thus, we propose that Set1C cooperates with Swi6 and heterochromatin to direct donor choice to mat2-P in M cells, perhaps by inhibiting the SRE3 recombination enhancer, and that in the absence of Swi6 other factors are still capable of imposing biases to donor choice.